2021
DOI: 10.3390/jdb9030025
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in SIX1 Associated with Branchio-oto-Renal Syndrome (BOR) Differentially Affect Otic Expression of Putative Target Genes

Abstract: Several single-nucleotide mutations in SIX1 underlie branchio-otic/branchio-oto-renal (BOR) syndrome, but the clinical literature has not been able to correlate different variants with specific phenotypes. We previously assessed whether variants in either the cofactor binding domain (V17E, R110W) or the DNA binding domain (W122R, Y129C) might differentially affect early embryonic gene expression, and found that each variant had a different combination of effects on neural crest and placode gene expression. Sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 73 publications
(189 reference statements)
0
12
0
Order By: Relevance
“…Within these epiblast modules, unsurprisingly we note the expression of important placodal and non-neural genes Tfap2c , Homer2 and the BMP inhibitor Bambi . Alongside these markers, we also find the pluripotency marker Sall4 and Tspan13 , with the latter shown to be positively regulated by Six1 (Mehdizadeh et al, 2021). A recent study in chick suggests that based on transcriptional profiling a ‘pre-border’ state can already be defined prior to gastrulation.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Within these epiblast modules, unsurprisingly we note the expression of important placodal and non-neural genes Tfap2c , Homer2 and the BMP inhibitor Bambi . Alongside these markers, we also find the pluripotency marker Sall4 and Tspan13 , with the latter shown to be positively regulated by Six1 (Mehdizadeh et al, 2021). A recent study in chick suggests that based on transcriptional profiling a ‘pre-border’ state can already be defined prior to gastrulation.…”
Section: Discussionmentioning
confidence: 77%
“…GM21 displays similar dynamics but is restricted to non-neural clusters somewhat earlier (HH5; Figure 3A). Although some genes within these epiblast modules have been described as non-neural/PPR specific based on in situ hybridisation ( Tfap2c , Bambi , Homer2 , Tspan13 ) (Bell et al, 2004; Hintze et al, 2017; Mehdizadeh et al, 2021; Reichert et al, 2013; Rothstein & Simoes-Costa, 2020), others are found to be expressed within the early neural territory ( Epcam , Sall4 , Cited4 ) (Barembaum & Bronner-Fraser, 2007; Bell et al, 2004; Trevers et al, 2021) (Figure 3–Source Data 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors posit that these cell lines will serve as a reliable, patient-specific platform with which to understand the cellular processes that are affected in MS. The variants associated with another craniofacial syndrome, Branchio-Oto-Renal (BOR) syndrome, were investigated by Mehdizadeh et al [ 12 ]. They expressed the homologues of four different human variants of SIX1 (BOR) in wild-type Xenopus embryos to model this autosomal dominant disease in which patients express one wild-type allele and one mutant allele.…”
mentioning
confidence: 99%
“…Tavares and Moody are coauthors of one of the publications included in the special issue [ 12 ]. The funders had no role in the design of the study; in the collection, analyses, or interpretation of data; in the writing of the manuscript, or in the decision to publish the results.…”
mentioning
confidence: 99%